Finite-Element Analysis of Vertical Displacement of Laminated Rubber Bearing under Earthquake Action for Disaster Resilience of the Smart City - Denglian Yang; Yanli Liu (Journal of Advanced Transportation)
With the construction and development of smart cities, higher requirements have been put forward for the prediction and control of major natural disasters. For the prevention of earthquake disasters in super high-rise buildings, the rubber bearings of high-rise seismic isolation structures may have the risk of tensile damage in high-intensity areas, which has always been an urgent problem to be solved. In this paper, a unidirectional horizontal compression-shear experiment with 400% large deformation was conducted on the laminated rubber bearing (LNR500), and the relationship curve of vertical displacement with horizontal displacement of the bearing was obtained. According to the experimental data, an ideal elastic-plastic principal structure model was selected for the steel and a Yeoh principal structure model was selected for the rubber material, and the finite element analysis was carried out for the bearing. The time course curves of displacement, velocity and acceleration of the vertical and horizontal deformation of the laminated rubber bearing under the earthquake were obtained.